Predictive Factors of Acute Symptomatic Seizures in Patients With Ischemic Stroke Due to Large Vessel Occlusion - Tako, Lisa Marie; Strzelczyk, Adam; Rosenow, Felix; Pfeilschifter, Waltraud; Steinmetz, Helmuth; Golbach, Rejane; Schäfer, Jan Hendrik; Zöllner, Johann Philipp; Kohlhase, Konstantin (Frontiers in Neurology, 2022)
IIntroduction: Acute symptomatic seizure (ASz) after ischemic stroke is associated with increased mortality; therefore, identifying predictors of ASz is important. The purpose of this study was to analyze predictors of ASz in a population of patients with ischemic stroke due to large arterial vessel occlusion (LVO). Materials and methods: This retrospective study examined patients with acute ischemic stroke caused by LVO between 2016 and 2020. Identification of predictive factors was performed using univariate and subsequent multiple logistic regression analysis. In addition, subgroup analysis regarding seizure semiology and time of seizure occurrence (≤ 24h and > 24h after stroke) was performed. Results: The frequency of ASz among 979 patients was 3.9 % (n = 38). Univariate logistic regression analysis revealed an increased risk of ASz in patients with higher National Institutes of Health Stroke Scale (NIHSS) score at admission or 24 hours after stroke, hypernatremia at admission ≥ 145 mmol/L, and pneumonia. Further multiple logistic regression analysis revealed that NIHSS 24 hours after stroke was the strongest predictor of ASz, particularly relating to ASz occurring later than 24 hours after stroke. Patients who experienced a seizure within the first 24 hours after stroke were more likely to have a generalized tonic-clonic (GTCS) and focal motor seizure; beyond 24 hours, seizures with impaired awareness and non-convulsive status epilepticus were more frequent. Conclusion: NIHSS score 24 hours after stroke is a strong predictive factor for the occurrence of ASz in patients with ischemic stroke caused by LVO. The semiology of ASz varied over time, with GTCS occurring more frequently in the first 24 hours after stroke.